Exploration of Traumatic Tenets in 9/11 Novels - Thapa, Rashmi (Patan Prospective Journal, 2025)
The terrorist incidents of September 11, 2001 transformed global political dialogue, cultural remembrance, and modern literature. In reaction, a genre of literature termed “9/11 novels” surfaced, examining trauma, grief, identity, nationalism, and the changes in personal and societal life following the attacks. This study analyzes significant themes, storytelling methods, and portrayal difficulties present in chosen 9/11 novels—including Jonathan Safran Foer’s Extremely Loud & Incredibly Close, Don DeLillo’s Falling Man, and Mohsin Hamid’s The Reluctant Fundamentalist. The study additionally examines how these works address trauma, memory, intercultural conflict, and evolving concepts of home, belonging, and security. Results indicate that 9/11 literature significantly influences public perceptions of the incident and its consequences, providing creative avenues for mourning, discussion, and cultural analysis. The literature that arose following the September 11, 2001 terrorist attacks showcases intricate emotional, political, and cultural reactions. Referred to as 9/11 fiction or post-9/11 literature, these creations seek to comprehend an event that was shocking, traumatic, and of global significance. Their examination encompasses topics of trauma, identity, national memory, and the moral considerations of representation.